NoMadCar: the interactive design using human computer interaction techniques - Shaikh, Asadullah; Soomro, Safeeullah; Shah , Asadullah; Aziz, Abdul (2012)
Human Computer Interaction (HCI) is playing a vital role in the design of several interfaces such as computer softwares, games, virtual reality, car steerings etc. In today's world people want to use mobile devices while deriving that may result an accident due to the loss of attention. Therefore, this paper presents the design that is used to nd the ways how a user interface in the car can improve the driver's safety when using mobile devices such as phones and mp3 players while driving. The paper concentrates on two elements that contribute to that goal. The rst one is the development of a user interface that enables the driver to control all the needed functions of mobile devices from the car's controls without actually having to touch the device itself. The second is the utilization of automatic driving assistance systems that aect the driving behavior of the car